The Relationship Between Transformational Leadership, Work-Life Balance, and Employee Performance with Job Satisfaction as a Mediating Variable - I Made Adhika; I Wayan Widnyana; Ni Made Dwi Puspitawati; Ni Wayan Mita Ekariani (AIBPM Publisher, 2025)
The productivity decline and high absenteeism among employees at UD Dewa Dewi Busana Denpasar in 2024 highlight internal issues that may affect performance and job satisfaction. This study examines the influence of transformational leadership and work-life balance on employee performance, with job satisfaction as a mediating variable. Using a quantitative approach and a census of 35 employees, data were collected through questionnaires and interviews, then analyzed using PLS-SEM with SmartPLS 4. Results show that transformational leadership (? = 0.216, t = 2.062, p = 0.042) and work-life balance (? = 0.298, t = 2.382, p = 0.019) significantly improve employee performance. Both also enhance job satisfaction—transformational leadership (? = 0.327, t = 4.057, p = 0.000) and work-life balance (? = 0.540, t = 5.848, p = 0.000). Job satisfaction itself positively affects performance (? = 0.534, t = 3.957, p = 0.000) and partially mediates the effects of transformational leadership (? = 0.175, p = 0.012) and work-life balance (? = 0.289, p = 0.002) on performance. These findings underscore the pivotal role of leadership and work-life balance in enhancing job satisfaction and optimizing performance, particularly in growing fashion retail businesses.